Exploring lemology teaching with “internet plus” flipped classroom pedagogy - Yu-Xin Cao; Shu-Lin Xia; Zheng-Yun Zhu; Fan-Rong Zeng; Hai-Ning Li; Ting-Ting Zhang; Yong-Juan Liu (BMC Medical Education, 2023)
Abstract Background To investigate the use of flipped classroom pedagogy based on “Internet plus” in teaching viral hepatitis in the lemology course during the COVID-19 epidemic. Methods This study included students from the clinical medicine general practitioner class at Nanjing Medical University’s Kangda College, with the observation group consisting of 67 students from the 2020–2021 school year and the control group consisting of 70 students from the 2019–2020 school year. The observation group used “Internet plus” flipped classroom pedagogy, while the control group used conventional offline instruction. The theory course and case analysis ability scores from the two groups were compared and analyzed, and questionnaire surveys were administered to the observation group. Result After the flipped classroom, the observation group had significantly higher theoretical test scores (38.62 ± 4.52) and case analysis ability scores (21.08 ± 3.58) than the control group (37.37 ± 2.43) (t = 2.024, P = 0.045) and (19.16 ± 1.15) (t = 4.254, P < 0.001), respectively. The questionnaire survey in the observation group revealed that the “Internet plus” flipped classroom pedagogy approach can help enhance students’ enthusiasm to learn, clinical thinking ability, practical application ability, and learning efficiency, with satisfaction rates of 81.7%, 85.0%, 83.3%, and 78.8%, respectively; 89.4% of students expressed hope that whenever physical classes resumed, the offline courses could be combined with this pedagogy approach. Conclusion The use of the “Internet plus” flipped classroom pedagogy technique for teaching viral hepatitis in a lemology course boosted students’ theory learning ability as well as their case analysis ability. The majority of students were pleased with this type of instruction and hoped that whenever physical classes resumed, the offline courses may be integrated with the “Internet plus” flipped classroom pedagogical approach.